The Impact of Javanese Language Habituation on Elementary School Students as an Effort to Preserve Regional Languages - Shoimatul Magfiroh; Much. Arsyad Fardani; Ika Ari Pratiwi (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
Regional languages play an important role in maintaining cultural identity and politeness values in a multicultural society. However, the use of Javanese, particularly the krama variety, has shifted among the younger generation due to the dominance of Indonesian in various social domains, including educational settings. This situation poses challenges in efforts to maintain regional languages, especially at the elementary school level, which is the phase in which students' language habits are formed. This study aims to analyze the impact of a Javanese language familiarization program on improving elementary school students' mastery of krama vocabulary and politeness as part of a regional language preservation strategy. The study used a descriptive qualitative approach with data collection techniques through observation, semi-structured interviews, and documentation. The research subjects included the principal, class teachers, and students at Pati Kidul 01 Public Elementary School. Data analysis was carried out through the stages of data reduction, data presentation, and interactive conclusion drawing. The results of the study indicate that the familiarization program, which is implemented routinely every Thursday, has an impact on increasing the use of krama vocabulary in formal communication in the classroom. Furthermore, there was an increase in students' politeness in terms of speech and attitude, demonstrated through the use of respectful expressions, more refined diction, and changes in nonverbal behavior in interactions with teachers. These findings imply that familiarizing yourself with Javanese can be an effective pedagogical strategy for strengthening communicative competence while supporting the ongoing maintenance of regional languages in formal educational settings.